(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The findings of the paper show that women workers are seeminglyempowered socially and economically through their involvement in corporatesector. But female workers face restrictions from their male family memberswhen they intend to join the industry, which is similar to structural violencewithin the household. Additionally, female workers face structural violencefrom the very beginning of their joining the garment industry.